2017
DOI: 10.5152/npa.2017.19482
|View full text |Cite
|
Sign up to set email alerts
|

Suggested Biomarkers for Major Depressive Disorder

Abstract: Currently, the diagnosis of major depressive disorder (MDD) mainly relies on clinical examination and subjective evaluation of depressive symptoms. There is no non-invasive, quantitative test available today for the diagnosis of MDD. In MDD, exploration of biomarkers will be helpful in diagnosing the disorder as well as in choosing a treatment, and predicting the treatment response. In this article, it is aimed to review the findings of suggested biomarkers such as growth factors, cytokines and other inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 180 publications
6
48
0
Order By: Relevance
“…In addition, other researchers have confirmed neuronal atrophy in the granular cell and pyramidal cell layers of the hippocampus, along with a reduction in hippocampal volume in both patients with depression and animal models (Abdallah et al, 2015;Hacimusalar and Eşel, 2018). Likewise, in this experiment, the weight of rat hippocampus decreased in response to CUMS, indirectly indicating hippocampal atrophy.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, other researchers have confirmed neuronal atrophy in the granular cell and pyramidal cell layers of the hippocampus, along with a reduction in hippocampal volume in both patients with depression and animal models (Abdallah et al, 2015;Hacimusalar and Eşel, 2018). Likewise, in this experiment, the weight of rat hippocampus decreased in response to CUMS, indirectly indicating hippocampal atrophy.…”
Section: Discussionsupporting
confidence: 77%
“…The main obstacles in this area may consist of the lack of a suitable animal model of depression, the inclusion of a set of biologically and clinically heterogeneous disorders in MDD, the presence of different subtypes and the continual change of this subgrouping, the high incidence of comorbidities of MDD with many other physical or psychiatric disorders, and the lack of specificity and sensitivity rates of a single biomarker. Many authors have suggested that a wider and multivariate approach could be more useful, including a combination of neuro-imaging, genetic, epigenetic, proteomic and metabolomic approaches (Hacimusalar and Eşel, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Biomarkers are quantifiable characteristics of biological processes, which could prove helpful in improving diagnostic objectivity of MDD and TRD as well as help in personalizing its treatment. For MDD, no specific biomarkers have yet been found, though several markers have been shown to be potential candidates, such as brain-derived neurotrophic factor (BDNF), interleukins (IL) 1 and 6, tumor necrosis factor (TNF), malondialdehyde (MDA), hypothalamic-pituitary-adrenal (HPA) activity, and cortisol responses [ 86 , 87 ]. Every biomarker as a standalone shows a low sensitivity and specificity, partly explained by the heterogeneity of MDD.…”
Section: Towards a More Personalized Dbs Treatment Approach For Trmentioning
confidence: 99%